Driving Sustainable Performance in the Digital Era: The Roles of Big Data Analytics, Green Investment, and Green Transformational Leadership - Yudhistira Adwimurti; Etty Murwaningsari; Mohamad Rohieszan Ramdan (INVEST : Jurnal Inovasi Bisnis dan Akuntansi, 2026)
The global sustainability paradox highlights the gap between extensive investments in digital transformation and green initiatives and the limited achievement of Sustainable Development Goals (SDGs), particularly in emerging economies such as Indonesia. Prior studies have largely examined Big Data Analytics (BDA) and Green Investment (GI) separately, producing inconsistent findings and offering limited insight into the role of leadership as a contextual factor. This study aims to analyze the effects of BDA and GI on Sustainable Performance (SP) and to evaluate the moderating role of Green Transformational Leadership (GTL) in Indonesian non-financial listed companies. This research adopts a quantitative design using panel data from 741 firm-year observations over the 2023–2024 period. Data were collected from annual and sustainability reports and measured using a content analysis–based disclosure index that captures the extent and quality of sustainability-related information. The hypotheses were tested through panel regression with interaction terms to examine moderation effects. The results indicate that both BDA and GI have significant positive impacts on SP. Furthermore, GTL not only directly enhances sustainability performance but also strengthens the effects of BDA and GI, confirming its role as a quasi-moderating variable. These findings suggest that leadership is a critical mechanism in translating digital capabilities and environmental investments into tangible sustainability outcomes. This study extends the Natural Resource-Based View and Dynamic Capabilities Theory by demonstrating the catalytic role of environmentally oriented leadership. Practically, it emphasizes the importance of aligning digital strategy, green investment, and leadership development to improve corporate sustainability performance.